Disparities in Reported Testing for 1p/19q Codeletion in Oligodendroglioma and Oligoastrocytoma Patients: An Analysis of the National Cancer Database - Zreik, Jad; Kerezoudis, Panagiotis; Alvi, Mohammed Ali; Yolcu, Yagiz U.; Kizilbash, Sani H. (Frontiers in Oncology, 2021)
Purpose A chromosomal 1p/19q codeletion was included as a required diagnostic component of oligodendrogliomas in the 2016 World Health Organization (WHO) classification of central nervous system tumors. We sought to evaluate disparities in reported testing for 1p/19q codeletion among oligodendroglioma and oligoastrocytoma patients before and after the guidelines. Methods The National Cancer Database (NCDB) was queried for patients with histologically-confirmed WHO grade II/III oligodendroglioma or oligoastrocytoma from 2011-2017. Adjusted odds of having a reported 1p/19q codeletion test for patient- and hospital-level factors were calculated before (2011-2015) and after (2017) the guidelines. The adjusted likelihood of receiving adjuvant treatment (chemotherapy and/or radiotherapy) based on reported testing was also evaluated. Results Overall, 6,404 patients were identified. The reported 1p/19q codeletion testing rate increased from 45.8% in 2011 to 59.8% in 2017. From 2011-2015, lack of insurance (OR 0.77; 95% CI 0.62-0.97;p=0.025), lower zip code-level educational attainment (OR 0.62; 95% CI 0.49-0.78;p<0.001), and Northeast (OR 0.68; 95% CI 0.57-0.82;p<0.001) or Southern (OR 0.62; 95% CI 0.49-0.79;p<0.001) facility geographic region were negatively associated with reported testing. In 2017, Black race (OR 0.49; 95% CI 0.26-0.91;p=0.024) and Northeast (OR 0.50; 95% CI 0.30-0.84;p=0.009) or Southern (OR 0.42; 95% CI 0.22-0.78;p=0.007) region were negatively associated with reported testing. Patients with a reported test were more likely to receive adjuvant treatment (OR 1.73; 95% CI 1.46-2.04;p<0.001). Conclusion Despite the 2016 WHO guidelines, disparities in reported 1p/19q codeletion testing by geographic region persisted while new disparities in race/ethnicity were identified, which may influence oligodendroglioma and oligoastrocytoma patient management.